Confused About Theoretical Sampling? Engaging Theoretical Sampling in Diverse Grounded Theory Studies. (May 2020) - Conlon, Catherine; Timonen, Virpi; Elliott-O'Dare, Catherine; O'Keeffe, Sorcha; Foley, Geraldine
Theoretical sampling is a key procedure for theory building in the grounded theory method. Confusion about how to employ theoretical sampling in grounded theory can exist among researchers who use or who want to use the grounded theory method. We illustrate how we employed theoretical sampling in diverse grounded theory studies and answer key questions about theoretical sampling in grounded theory. We show how theoretical sampling functions in grounded theory and how it differs from sampling for data generation alone. We demonstrate how induction, retroduction, and abduction operate in grounded theory and how memoing drives theoretical sampling in the pursuit of theory. We explicate how theoretical sampling can contextualize data to build concepts and theory. Finally, we show how theoretical sampling in grounded theory operates in secondary analysis to derive theory that goes beyond the original purpose of data collection.